Effect of soft contact lens wear on corneal biomechanical properties and corneal topography - Sapkota, Kishor (2015)
Purpose: The aim of this study was to investigate the effect of soft CL wear on corneal hysteresis (CH) and corneal resistance factor (CRF). Effect of corneal topographic indices on CH and CRF was also determined. Methods: Thirty-one myopic subjects were fitted with a daily disposable (Nelfilcon A or Stenofilcon A) in one eye and a monthly disposable (Lotrafilcon B or Comfilcon A) in the other eye. Corneal biomechanical properties (CH and CRF) were measured with Ocular Response Analyzer.and corneal topographic indices (anterior surface curvature (simK), eccentricity, surface asymmetry index (SAI) and surface regularity index (SRI)) were measured with the corneal topographer Medmont E 300 before and after three months of CL wear. Changes in corneal biomechanical properties and it’s relation with corneal topographic indices, CL materials and lens wear modality were determined. Results: Sixty-two eyes of 31 subjects with mean age 23.6±3.3 years were included. Twenty of them (64.5%) were females. There was no change in CH (p = 0.799) but there was a reduction in CRF by 0.71±1.00 mmHg (p < 0.001). Reduction in CRF was correlated with the baseline CRF (r = 0.598, p < 0.001) but not with power of lens and number of wearing hours per day (p > 0.05). It was not associated with lens materials, lens wear modality and gender of the subjects (p > 0.05). Although corneal curvature flattened by 0.004±0.07mm, SAI and SRI decreased by 0±0.07, 0.03±0.40 and 0.03±0.33 respectively; all of these changes were statistically non-significant (p > 0.05). Change in CRF was correlated with change in SRI (r = 0.297, p = 0.021) but it was not correlated with change in curvature, SAI and eccentricity (p > 0.05). Conclusion: Three months soft CL wear reduces CRF but it does not change CH. The change in CRF was not associated with the lens materials and lens wear modality. It also was not correlated with changes in corneal topographic indices except a weak correlation with change in SRI.